NEGOTIATING POLITENESS IN ENGLISH-MEDIATED HERITAGE TOUR GUIDING AT MANGKUNEGARAN PALACE - Budi Purnomo (PARADIGM: Journal of Language and Literary Studies, 2026)
Politeness plays a central role in English-mediated heritage tour guiding, particularly in English as a Lingua Franca (ELF) setting where guides and tourists often come from diverse linguistic and cultural backgrounds. In such intercultural encounters, guides must balance cultural explanation, visitor engagement, rapport management, and mutual understanding. This study investigates how politeness is negotiated in guiding interactions at Surakarta Mangkunegaran Palace from a socio-pragmatic perspective. Data were collected through on-site audio recordings, field observations, and follow-up interviews with three professional guides. The findings reveal that guides employ a dynamic combination of politeness strategies, including hedging, softening, indirectness, humour, quiz-based engagement, and culturally grounded forms of Javanese politeness. These strategies enable guides to perform multiple roles as educators, entertainers, cultural mediators, and tour-flow managers while accommodating the needs of international visitors. The analysis further shows that politeness is interactionally co-constructed rather than realized through fixed linguistic formulas. The study contributes to politeness and intercultural pragmatics research by demonstrating how local Javanese values are recontextualized within ELF communication, producing hybrid forms of hospitality discourse. Practically, the findings highlight the importance of pragmatics-informed training for heritage tour guides working in intercultural environments.